Divine Institutions : Religions and Community in the Middle Roman Republic - Padilla Peralta, Dan-el (Princeton University Press, 2020)
Cover -- Title Page -- Copyright Page -- CONTENTS -- Abbreviations -- List of Figures, Plates, and Tables -- Acknowledgments -- 1 Introduction: One State, under the Gods -- I. The Middle Republic: Era of Transformations -- II. Periods and Periodicity -- III. Mid-RepublicanReligion as Stand-AloneCategory -- IV. The Road -- PART I. BUILD -- 2 Temple Construction: From Vows to Numbers -- I. Why and How Were Temples Built? -- II. The Human Investment in Temples: Scale and Inputs -- III. Testing the Model: Internal and External Comparanda -- IV. Conclusion -- 3 Temples and the Civic Order: From Numbers to Rhythms -- I. Praeda and the Genesis of Infrastructural Power -- II. Public Goods A: Civic Upkeep -- III. Public Goods B: The Regularization of Festival Culture -- IV. Conclusion -- PART II. SOCIALIZE -- 4 Temples, Festivals, and Common Knowledge: From Rhythms to Identities -- I. Performative Festival Culture as Social Technology -- II. Dramatic Festival Culture and the Propagation of Knowledge: Three Studies -- III. Conclusion -- 5 Pilgrimage to Mid-RepublicanRome: From Dedications to Social Networks -- I. Pilgrimage in Mid-RepublicanItaly: Prolegomena -- II. Anatomical Votives and Italy's Pilgrimage Networks -- III. Pottery and Pilgrims: The Religious Life of Souvenirs -- IV. Mid-RepublicanPilgrimage as Network Activity -- V. Conclusion -- 6 Conclusion: Religion and the Enduring State -- I. Prodigy Expiation and State Coordination -- II. Rhythm and Quantity: The Magnitude of the Consensus -- Color Plate -- III. Envoi -- Appendix: The Pocola Deorum: An Annotated Catalog -- References -- Index.